CALCULATION OF THE BRACER PIPELINE - Кравцов, В.; Комаров, В.; Чкана, Я. (Science-based technologies, 2012)
It is shown the method of calculation of increase of durability and reliability of underground pipelines of large-break is offered through banding at transporting of oil and gas. An analysis over is brought and short description of method is given. Considered features to the coiling bracer on pipe-basis. Presented results of calculations of the shrouded pipeline by means of the offered methods, got values of internal efforts and moments in dimensionless sizes.